PENGARUH MOTIVASI , KEMAMPUAN DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA ANGGOTA DALMAS POLDA JATENG - Ribut Hadi Handoko, 06.3502.0746; Maskur, Ali (Students Journal of Economic and Management, 2013)
The Purpose of this study was to implementation to test and analyze the influence of motivation, ability to work and organizational commitment to the performanceof police A study was conducted in Central Java Police Sub Dalmas totaling 137 Pirponsive using the criteria of the lowest rank of Brigadier. The result of regression testing obtained result Adjustment R Square of 0,787, meaning that change of variables can be explained by the variable performance of work motivation, job ability and of 87,7% organizational commitment while for the F test showed that motivation to work together, work ability and commitment affect organizational performance.Based on the known partial regression testing motivation affect performance with significance 0,0 06 < 0,05, the ability to work on performance with significance 0,013 < 0,05 and commitment affect organizational performance with significance 0,000.< 0,05.it is identifed that all the hypotheses accepted or proven.